Aktivitas Siswa dalam Penerapan Model Pembelajaran Inkuiri pada Mata Pelajaran IPS Siswa Kelas VIII Smp N 29 Semarang Tahun Ajaran 2018/2019 - suprapto, Mohammad Nur; Tjahjono, Heri; Suroso, Suroso (Edu Geography, 2018)
The purpose of this study is to find out how students' activities in the application of inquiry learningmodels in social studies subjects. The population of this study was all eighth grade students with 8classes. In this study the sampling technique used random sampling. The sample was taken from25% of the study population. Because the sample is considered homogeneous so that in sampling tofacilitate research taken from two classes randomly selected from the selection obtained classes VIIIC and VIII D. Data collection techniques used were questionnaires. Data analysis techniques usingdescriptive analysis. The results showed the level of student learning activities in Inquiry learningincluded the criteria of less active, indicated by the activities of students in orientation, formulatingproblems, collecting data and testing hypotheses, classically 46% of students' active activities, and54% less active. Tujuan dari penelitian ini untuk mengetahui bagaimana aktivitas siswa dalam penerapanmodel pembelajaran inkuiri pada mata pelajaran IPS. Populasi penelitian ini adalahseluruh siswa kelas VIII yang jumlahnya ada 8 kelas. Dalam penelitian ini teknikpengambilan sampel menggunakan random sampling.Sampel penelitian ini diambil dari25% dari populasi penelitian. Karena sampel dianggap homogen sehingga dalampengambilan sampel untuk memudahkan penelitian diambil dari dua kelas yg dipilihsecara acak dari pemilihan tersebut diperoleh kelas VIII C dan VIII D. Teknikpengumpulan data yang digunakan adalah angket. Teknik analisis data menggunakananalisis deskriptif. Hasil penelitian menunjukkan tingkat aktivitas belajar siswa dalampembelajaran Inquiry termasuk kriteria kurang aktif, ditunjukkan dengan aktivitas siswadalam orientasi, merumuskan masalah, mengumpulkan data dan menguji hipotesis,Secara klasikal aktivitas belajar siswa 46% Aktif, dan 54% kurang Aktif.